dwt 2017
DOI: 10.5004/dwt.2017.20236
|View full text |Cite
|
Sign up to set email alerts
|

Performance comparison between overlapped and woven spacers for membrane distillation

Abstract: a b s t r a c tThe sustainable production of freshwater from seawater desalination is receiving increasing attention. Recently, some desalination technologies are taking advantage from the coupling with renewable resources; among them, membrane distillation (MD) is one of the most promising since it can be easily powered by low-grade thermal energy. MD being an emerging technology, efforts are required to optimize geometry and operating conditions of real units in order to reduce the unitary freshwater product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
5
1
Order By: Relevance
“…Unsteadiness and transition to turbulence were also studied for the same geometry by time-dependent direct numerical simulation [17]. In comparison with the corresponding nonwoven spacers, the woven ones exhibited better mixing at the investigated flow attack angles of 0 and 45° [18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Unsteadiness and transition to turbulence were also studied for the same geometry by time-dependent direct numerical simulation [17]. In comparison with the corresponding nonwoven spacers, the woven ones exhibited better mixing at the investigated flow attack angles of 0 and 45° [18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The ED/RED model here adopted can be used for the three electromembrane processes considered in this paper. It uses a one-dimensional representation of the stack, but it includes also local results from 3-D Computational Fluid Dynamics (CFD) simulations (friction coefficients [40][41][42], mass transfer coefficients [43,44], and Ohmic resistances). This coupling between CFD and a one-dimensional model was already presented in previous works [45,46].…”
Section: Electromembrane Processes Modelmentioning
confidence: 99%
“…In regard to the spacer geometry, in the feed channel of an RO module, usually non-woven spacers are adopted [47][48][49]. Due to the lack of detailed data on the spacer geometry adopted in the commercial RO modules considered in this work, we used a friction factor value obtained from previous CFD simulations of overlapped spacers reported in [42]. In the range of the Reynolds numbers investigated here (100-300), the friction factor for the overlapped spacer with an orientation of 45° with respect to the flow, can be estimated as 𝑓 ≈ 10 ‱ (96 𝑅𝑒 ⁄ ).…”
Section: 𝑄 = 𝑄mentioning
confidence: 99%
“…Therefore, most of the ongoing research on better spacer designs is focused on the double purpose of increasing the fluid mixing, and thus, the heat transfer coefficients, while keeping the frictional pressure losses within the acceptable values [7][8][9][10][11]. A comparison of two of the most popular spacer designs, i.e., the overlapped and woven ones, is given by Gurreri et al [12] for a pitch-to-height ratio P/H = 2. The results showed that the woven spacers provided higher Nusselt numbers, but there were also higher friction coefficients with respect to the overlapped spacers.…”
Section: Introductionmentioning
confidence: 99%